Role of African-American Fathers in Child-Rearing and Oral Health Practices in an Inner City Environment - A Brief Communication - Hillary Broder, PhD; Susan Reisine, PhD; Robert Johnson, MD (Blackwell Synergy, 2006)
This study assesses parenting behaviors, health behaviors and attitudes in a sample of disadvantaged African-American fathers and evaluates the potential of fathers as recipients of oral health promotion interventions.